Guide to Targeted Therapies: Treatment Resistance in Lung Cancer - Cappuzzo, Federico; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Adis, 2015)
This text is a concise and up-to-date review, which discusses the background, development and mechanisms of resistance, testing methods and technology, current and emerging therapies and resources that clinicians can provide to their patients. Busy healthcare professionals who want a quick review of treatment resistance in lung cancer as well as a summary of current therapies will benefit from this succinct guide.
Introduction -- Therapy options for advanced NSCLC -- Resistance to EGFR TKIs -- Overcoming EGFR-TKI resistance -- Resistance to crizotinib and therapeutic options -- Resistance to angiogenic drugs and therapeutics options.- Conclusions.
Keywords: Oncology .; Oncology